Electrophysiological evaluation of peripheral neuropathy in chronic kidney disease patients: A study from tertiary care centre, Maharashtra - Gajanan Gondhali1 , J.K. Deshmukh2 , Ashish Kundalwal3 , Anant A. Takalkar4 (Perspectives In Medical Research, 2020)
Introduction: CKD has turned a major cause of morbidity and mortality. The prevalence of peripheral neuropathy is directly proportional to duration and severity of CKD. Peripheral neuropathy becomes evident after the patient reaches stage 4 CKD, but electrophysiological evidences occurs earlier. NCS is an important means of evaluating the functional integrity of peripheral nerves and has implications regarding clinical course and prognosis. Objectives: To study electrophysiological findings of peripheral neuropathy in CKD patients Methodology: The present study was a cross sectional; descriptive study was conducted in October 2016 to October 2018. Data analysed by using SPSS 23.0 version. Clinical and neurological examinations were done and blood investigations were performed following which NCS was done. Results: Out of 90 subjects, majority were from 45-54 years age group (26). 70% were male and 30% were females. Total 10 (11.11%) patients showed pure sensory type of PN. Total 47 (52.22%) patients showed sensory-motor type of PN. sensory-motor type of PN was the predominant type (52.22%) found in study followed by pure sensory type of PN (11.11%). Pure axonal sensory motor pattern of PN found in 15 (25%) patients in preHD group, 11 (36.66%) patients in HD group. The difference between the pre-HD and HD groups were statistically significant for the median nerve amplitude, common peroneal nerve CV, posterior tibial nerve CV, posterior tibial nerve distal latency and sural nerve distal latency (p < 0.05). Conclusion:Peripheral neuropathy is very common in CKD, more common in dialysis patients as compared to predialysis patients. It’s frequency and severity increase as the duration of disease and stage of CKD increases. Sensory motor type of neuropathy is more common than pure sensory type of neuropathy.Pure axonal sensory motor and mixed (axonal + demyelinating) sensory motor neuropathy are common patterns of PN in CKD.